ANALISIS WILLINGNESS TO PAY MASYARAKAT TERHADAP UPAYA PELESTARIAN LINGKUNGAN SUNGAI LEARISA KAYELI DI NEGERI HARUKU - Papilaya, Renoldy Lamberthy; Payer, Matheus Tristan (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2026)
This study was conducted with the aim of: (1) Identifying the existing conditions of the economic utilization of the Learisa Kayeli River in Haruku Village, (2) Knowing the economic value of the Learisa Kayeli River based on the willingness to pay (WTP) of the people of Haruku Village in efforts to preserve the environment of the Learisa Kayeli River, (3) Analyzing the variables that influence the willingness to pay (WTP) of the people of Haruku Village in efforts to preserve the environment of the Learisa Kayeli River. This study was conducted in Haruku Village, Central Maluku Regency, using a survey method. The sampling method used saturated sampling for the community (head of family) and purposive sampling for the government staff of Haruku Village, Saniri Villagei, and Kewang. The data analysis method used was a qualitative descriptive method, the Contingent Valuation Method (CVM) approach, and multiple linear regression which also contained an analysis model with dummy variables. Based on the research results, it was found that the existing conditions for economic use of the Learisa Kayeli River consist of: (1) Open sasi lompa area, (2) Speed boat anchorage , and (3) Maleo bird habitat. The total value of the willingness to pay of the Haruku Village community in efforts to preserve the Learisa Kayeli River environment is IDR 30,465,000 per month. The variables that influence the WTP of the Haruku Village community in efforts to preserve the Learisa Kayeli River environment are income, length of stay, and occupation, while the variables that do not influence the community's WTP are age, education, gender, and knowledge of the river.